Implementing the Pancasila Rahmatan lil Alamin Student Profile Strengthening Project: A GESI-Based Analysis of Gender Equality and Social Inclusion in Madrasah Education - Awwiby Awfara Ahya; Tri Marhaeni Pudji Astuti; Puji Lestari (Ilmu Inovasi Nusantara, 2025)
The Pancasila Rahmatan lil Alamin Student Profile Strengthening Project (P5PPRA) represents a key initiative of the Merdeka Curriculum to foster students' competencies and character development through a project-based learning approach. This study explores the implementation of the P5PPRA program at MAN Grobogan Regency, focusing on students’ social construction of gender roles and inclusion, analyzed from the perspective of Gender Equality and Social Inclusion (GESI). The study also evaluates how the GESI framework supports gender equality and social inclusion within the madrasah setting. The study employed data collection techniques using a qualitative research design, including in-depth interviews, focus group discussions (FGDs), and direct observations. Research participants included students, teachers, and madrasah administrators from MAN 1 Grobogan and MAN 2 Grobogan. The findings reveal that the P5PPRA program provides equitable opportunities for student participation, reflecting a positive step toward inclusion. However, entrenched gender stereotypes continue to shape the division of roles in project groups. Male students predominantly assume technical or physical tasks, while female students are more often relegated to administrative responsibilities. This pattern highlights the persistent influence of societal gender norms on students' social construction. GESI implementation within the two madrasahs demonstrates significant progress in ensuring accessibility and participation for all students. Nonetheless, challenges remain in fostering an entirely equitable and inclusive environment, particularly in the balanced allocation of roles and responsibilities. To address this, future initiatives should incorporate targeted strategies to dismantle gender norms and enhance inclusive practices across all project activities